Islamic Financing Institutions in Indonesia: Concepts, Regulations, and Financing Products - Tulhasanah, Nopa; Wahyuni, Teni (EJESH: Journal of Islamic Economics and Social, 2025)
The dynamic evolution of the global economy necessitates a financial system that is not only efficient but also just and ethical. In this context, Islamic financial institutions emerge as a strategic alternative by offering financial solutions grounded in Islamic principles such as justice, transparency, and social responsibility. This study aims to examine the concepts, regulations, operational principles, and various Islamic financing products developing in Indonesia. Employing a library research method, this study draws on academic literature, official regulations, and fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The findings reveal that Islamic financial institutions perform financial intermediation through Sharia-compliant contracts such as murabahah, mudharabah, musyarakah, ijarah, and others. In terms of regulation, these institutions operate under a formal legal framework that includes Law No. 21 of 2008, Minister of Finance Regulation No. 84/PMK.012/2006, various regulations from the Financial Services Authority (OJK), and Sharia fatwas. The financing products offered encompass consumptive, productive, syndicated, take-over, and letter of credit (L/C) financing. The study underscores the significant role of Islamic financial institutions in promoting inclusive and sustainable economic growth in Indonesia